Hybrid block truncation coding for color image compression - Jun Wang; Yeun-Cheul Jeung; Jong-Wha Chong (2009 IEEE International Conference on Network Infrastructure and Digital Content, 2009)
In this paper, a hybrid block truncation coding (HBTC) is presented for color image compression. In the HBTC algorithm to improve the compression ratio of the basic BTC, only luminance bit-map is employed to represent the edge information of the coding block. Moreover, an efficient previous proposed algorithm, adaptive quantization coding (AQC), is used to compress the two representative levels further. Simulation results show that the proposed HBTC performs as well as the BTC in terms of subject visual quality, and significantly improves the compression ratio of BTC from 2.88:1 to 6.00:1 with the limited performance losing about 0.66 dB in PSNR.